A saddlepoint approximation to the distribution of the sum of independent non‐identically beta random variables. (17th October 2014) - Nadarajah, Saralees; Jiang, Xiao; Chu, Jeffrey
<x xml:space="preserve">Abstract</x> The exact distribution of the sum of more than two independent beta random variables has not been known. Even in terms of approximations, only the normal approximation is known for the sum. Motivated by Murakami [Statistica Neerlandica, 2014, doi:10.1111/stan.12032], we derive here a saddlepoint approximation for the distribution of sum. An extensive simulation study shows that it always performs better than the normal approximation.